Critical Discourse Analysis of the Role of the PPKS Task Force in Reporting Sexual Violence in Kompas.id Media - Raden Ajeng Fidia Haulah; Zikri Fachrul Nurhadi; Ismira Febrina; Hamizah Sahharon (Communicatus: Jurnal Ilmu komunikasi, 2025)
The sexual violence case involving a lecturer at the University of Mataram has garnered significant public and media attention. The coverage of the lecturer's dismissal not only revealed the facts surrounding the incident but also highlighted the role of the PPKS Task Force in handling the case and the media's role in shaping the narrative. This study explores the role of the PPKS Task Force in the discourse presented by Kompas.id media. Using a qualitative descriptive method and Teun A. Van Dijk's critical discourse analysis theory, data were collected through literature review, interviews, and documentation. The findings show that the textual structure used by Kompas.id effectively constructs a narrative that influences public perception, indicating media bias in favor of the institution (Unram). The role of the PPKS Task Force at the University of Mataram, as reported by Kompas.id, is consistently portrayed as taking firm action against perpetrators. The Task Force is represented as a key institution in the prevention and handling of cases involving victims. Renaming the PPKS Task Force to the PPKPT Task Force marks a new focus on preventing violence within educational environments